Analyze Factors Affecting Room Pricing of Accommodation in Luang Prabang Province: https://doi.org/10.69692/SUJMRD0901374 - XAYSONGKHAM, Chendavanh; ANOUSINH, Soutthida; SAYNAVONG, Neevanh; SOUKAVONG, Bounthone; SENGCHANH, Souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study of “Analyze Factors Affecting Room Pricing of Accommodation in Luang Prabang Province”. The objectives of the study are the overview Luang Prabang tourism, hotel and guesthouse statistics, in particular to investigate the way which room rates are determined. Data was collected from Agoda website by survey in May 2108. The sample size is 204 hotel and guesthouse that consists of 1,326 observations. Based on Hedonic Pricing Model for estimation and data analyzing for Ordinary Least Square (OLS) by Stata 13. Our result of finding included that there were 643,319 tourists (2016) from domestic and foreign countries. The total number of hotels and guesthouses accounted for 415 (2016) which includes 65% and 35% of domestic and foreigner firms respectively. The room rates of hotel and guesthouse are between $ 2 and $ 400 per night. The results illustrate that the factors determined the hotel and guesthouse room rates in Luang Prabang are 17 variables; for instance, colonial style, deluxe room, river view, room size, number of rooms, guest limited, bed king, wooden parquet floor, free cancellation, car park, front desk 24 hours, swimming pool, and massage. Which these variables are most statistically significant. Furthermore, the symbol of variables is similar on our prediction; expecting some variables are the heritage site area, Wi-Fi and 24 hours security which is not statistically significant. In addition, Free airport transfer service is statistically significant; apart from, the symbol of variable is not the same on our prediction.